A Mulher e as artes: as pintoras da Primeira República no Rio de Janeiro - Oliveira, Míriam Andréa de (1998)
The goal of our research is to study the social origins and the cultural background of the women painters who participated of the General Exhibitions of the National School of Fine Arts located in Rio de Janeiro. Our thesis is included in the perspective of cultural history and based on an interdisciplinary approach to understand the women painters' position in the Brazilian Society of the turn of the century, their image of the world and of themselves, reflected in the images and paintings. The study of the lives of a sample of 209 artists revealed that realism prevailed in their style and the predominant thems of their paintings were taken from daily life of the bourgeoisie, to which most them belonged. The analisis of these artists is developed within the framework of the cultural background of the Brazilian republic and its contemporary reflections.